1990
DOI: 10.1177/106002809002401014
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Drug Interactions: A Review of the Literature

Abstract: This article provides a historic overview of drug interaction screening and reviews 19 studies that have sought to measure the frequency of drug interactions. Differences in study designs, methodologies, and definitions contribute to considerable variation in the reported incidence rates, which ranged from 2.2 to 70.3 percent for all potential drug interactions. The percentage of patients actually experiencing symptoms that could be attributed to a drug interaction, however, ranged from 0 to 11.1 percent. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 15 publications
3
29
0
1
Order By: Relevance
“…28,[30][31][32][33][34] However, because safety problems may be underrecognized and underreported, we encourage all health care providers to question patients about dietary supplement use, especially because there are increasing reports of significant morbidity and mortality, with or without concomitant pharmaceutical use. 9 In addition, health care providers should consider potential drug-dietary supplement interactions, regardless of the severity of the potential interaction, because even minor interactions can affect drug therapy and patient quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,[30][31][32][33][34] However, because safety problems may be underrecognized and underreported, we encourage all health care providers to question patients about dietary supplement use, especially because there are increasing reports of significant morbidity and mortality, with or without concomitant pharmaceutical use. 9 In addition, health care providers should consider potential drug-dietary supplement interactions, regardless of the severity of the potential interaction, because even minor interactions can affect drug therapy and patient quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Although our incidence rates may seem low at first glance, these results correspond reasonably well with the 2% to 3% estimate of severe drug-drug interactions noted by Peterson and Bates, 30 and approximate the range of incidence rates seen for potentially serious drug-drug interactions found in various ambulatory populations. 28,[30][31][32][33][34] Since our study was initially completed in 1999, we considered that newer information on interactions might alter the incidence rate of potentially serious interactions. To address this, we completed a second MEDLINE search in late 2001 and also reassessed our findings using a more contemporary, comprehensive reference on drug-dietary supplement interactions.…”
Section: Commentmentioning
confidence: 99%
“…Reported incidences in outpatients range from 9.2% to 70.3% for drug interactions of any severity, and from 1.2% to 23.3% for those considered of major relevance [5][6][7][8][9][10][11]. A German primarycare study showed that of all observed major or moderate potential drug interactions only 11.7 % offered no management options, and such drug combinations should thus be avoided [12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of potential DDIs is far from trivial. 1,5,7,19,20 A study of pharmacy records from VA ambulatory care clinics found that the rate of exposure to 25 potential DDIs was 2.2%. 20 Another study on the frequency of potential DDIs in a pharmacy benefits manager's drug database revealed that the potential DDI pair with the highest prevalence rate (warfarin/non-steroidal anti-inflammatory drug) occurred at a rate of 279 per 100,000 persons.…”
Section: Discussionmentioning
confidence: 99%
“…DDIs occur in 9% to 70% of patients in the outpatient setting. 5 Computer programs and drug compendia are commonly used to assist pharmacists in recognizing drug interactions, but the usefulness of these tools is limited. For example, DDI software programs identify both clinically significant and nonsignificant drug interactions, making it challenging for pharmacists to interpret DDI warnings.…”
Section: Introductionmentioning
confidence: 99%